PENGARUH METODE BRAINWRITING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA PELAJARAN IPS KELAS V SDN 20 AMPENAN TAHUN AJARAN 2021/2022 - Daefatul Azizati; Safruddin Safruddin; Itsna Oktaviyanti (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
This research was conducted based on the results of observations at SDN 20 Ampenan, namely the low problem solving ability of students, especially in social studies subjects. This is because teachers tend to use the one-way (conventional) method and the teacher lacks variety in applying learning methods. Therefore, there is a need for an update in implementing the learning method, namely using the Brainwriting method. Based on this, this study aims to determine the effect of the Brainwriting method on problem solving abilities in social studies class V at SDN 20 Ampenan, Mataram District, in the 2021/2022 academic year. This research is a quantitative research with a quasi-experimental non-equivalent control group design. The sampling technique used is saturated sampling. The population and sample in this study were all students of class VB as the experimental class and students of class VA as the control class. Data collection methods used are observation, tests, and documentation. The instrument used is an observation sheet on the implementation of learning the Brainwriting method and a problem-solving ability test. In testing the instrument, the researcher used the expert validity test. The data analysis in this study begins with a normality test using the Kolmogrov Smirnov formula with a significance level of 5% (0.05) followed by homogeneity testing and research hypothesis testing. Then the problem solving ability data were analyzed by t-test to determine the research hypothesis. The results of data analysis showed that the value of sig.2 tailed was 0.000, which was less than 0.05, so based on the research hypothesis, if the value of sig.2 tailed was <0.05 t-table, then H0 was rejected and Ha was accepted. This shows that there is an effect of the Brainwriting method on problem solving abilities in social studies lessons for class V SDN 20 Ampenan for the 2021/2022 academic year.